METODE DISPROGRAMMING DALAM MENDESAIN PASAR IKAN DADAP - Fahmi Syafutra; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Geographically, Indonesia is an archipelago with a sea area larger than land, but unfortunately the potential of the coast has not been utilized properly. This is not an exception to Kampung Dadap, which is an area on the coast of the North Java coast that borders the Tangerang and DKI Jakarta Regencies. The majority of the people of Dadap Fishermen Village, who work as fishermen and roadside traders, do not have activity support facilities as a place for them to express their activities, so that their economic potential does not develop, making the fishermen's village appear to be a dead village due to lack of visitors. In responding to the problems that arise, this project aims to make the Fish Market a supporting facility for fishery activities that can attract visitors, which can improve the quality of life of the Dadap Fishermen Village community in dwelling, social and economic context. This project is aimed at all communities, especially around the Dadap Kosambi Fisherman Village area. With the modern market concept of "disprogramming method", it is hoped that the middle to lower and upper middle class people of the economy can join forces to form mutually beneficial activities. This project also provides supporting facilities that can invite newcomers to develop the economic potential of local residents and can improve the quality of life for fishing village communities. With this, the quality of life of the people of Kampung Nelayan Dadap, in the context of dwelling, social and economic life will improve. Key words: Disprogramming; Facility; Fishermen; Market; Village. AbstrakSecara geografis, Indonesia merupakan negara kepulauan dengan luas laut yang lebih besar dari daratan, Namun sayangnya potensi pesisir belum dimanfaatkan dengan baik. Hal ini tidak menjadi pengecualian bagi Kampung  Dadap  yang merupakan  suatu  wilayah  di  pesisir  Pantai  Utara  Jawa  yang  membatasi wilayah  Kabupaten  Tangerang  dan  DKI  Jakarta. Mayoritas masyarakat Kampung Nelayan Dadap yang berprofesi sebagai nelayan ikan tangkap dan pedagang di pinggir jalan, tidak memiliki fasilitas penunjang kegiatan sebagai wadah mereka untuk menuangkan aktivitasnya, sehingga potensi ekonominya tidak berkembang menjadikan kampung nelayan terkesan sebagai kampung mati karena sepi pengunjung. Dalam menjawab permasalahan yang muncul tersebut, proyek ini bertujuan untuk membuat Pasar Ikan sebagai fasilitas pendukung kegiatan perikanan yang dapat menarik pengunjung,  yang dapat meningkatkan kualitas hidup masyarakat Kampung Nelayan Dadap dalam konteks berhuni, sosial dan ekonominya. Proyek ini ditujukan untuk semua masyarakat terutama di sekitar kawasan Kampung Nelayan Dadap Kosambi. Dengan konsep pasar modern “metode disprogramming” diharapkan masyarakat kalangan ekonomi menengah ke bawah sampai menengah keatas dapat bergabung membentuk suatu aktivitas yang saling menguntungkan.  Proyek ini menyediakan pula fasilitas penunjang  yang dapat mengundang pendatang mengembangkan potensi ekonomi warga setempat dan dapat meningkatkan kualitas kehidupan  masyarakat kampung nelayan. Dengan ini kualitas hidup masyarakat Kampung Nelayan Dadap dalam konteks berhuni, sosial dan ekonominya dapat meningkat.